Identification of Vulnerable Zones for Groundwater Using a GIS-based DRASTIC Technique in Shwan Sub-basin/North-Iraq - Al-Hayali, Hussein Dheyaa; Al-Tamimi, Omer S. Ibrahiem; Hamamin , Dara Faeq (Iraqi Journal of Science, 2021)
Groundwater is considered as one of the most important sources of fresh-water, on which many regions around the world depend, especially in semi-arid and arid regions. Protecting and maintaining groundwater is a difficult process, but it is very important to maintain an important source of water. The current study aims to assess the susceptibility of groundwater to pollution using the DRASTIC model along with the GIS environments and its tool boxes. A vulnerability map was created by relying on data collected from 55 wells surveyed by the researchers as well as archived records from governmental institutions and some international organizations. The results indicate that the region falls into three vulnerability functional zones , namely very low, low and medium. Fortunately, most of the region is in a very low - low range (89-125) which covers approximately 94.6% of total area of the region, while the medium zone (125-133) forms 5.4%, as the smallest part of the total area ofregion. To reduce the risk of pollution in the medium zones of vulnerability, precautionary measures must be taken before commencing industrial or agricultural activities.